2021
DOI: 10.1002/cam4.3847
|View full text |Cite
|
Sign up to set email alerts
|

XRCC5/6 polymorphisms and their interactions with smoking, alcohol consumption, and sleep satisfaction in breast cancer risk: A Chinese multi‐center study

Abstract: Background X‐ray repair cross‐complementary 5 (XRCC5) and 6 (XRCC6) are critical for DNA repair. Few studies have assessed their association with breast cancer risk, and related gene‐environment interactions remain poorly understood. This study aimed to determine the influence of XRCC5/6 polymorphisms on breast cancer risk, and their interactions with cigarette smoking, alcohol consumption, and sleep satisfaction. Methods The study included 1039 patients with breast cancer and 1040 controls. Four single‐nucleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…This study sought to identify potential pathogenic genes associated with BC by constructing a BC gene interaction network. This study extended the results of prior studies [ 14 ] by not only assessing the effect of a single gene on BC but also the gene interaction network, providing new insight into how genetic factors impact complex human diseases. These results suggest that BMI and menopausal status may be risk factors for BC.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…This study sought to identify potential pathogenic genes associated with BC by constructing a BC gene interaction network. This study extended the results of prior studies [ 14 ] by not only assessing the effect of a single gene on BC but also the gene interaction network, providing new insight into how genetic factors impact complex human diseases. These results suggest that BMI and menopausal status may be risk factors for BC.…”
Section: Discussionsupporting
confidence: 58%
“…Low-grade systemic inflammation is one of the characteristics of obesity [ 38 ], and RETN is shown to exert pro-inflammatory properties by upregulating pro-inflammatory cytokines [ 39 ] through the NFκB signaling pathway [ 40 ] that lead to inflammation and tumorigenesis. Several studies have also linked XRCC6 with an increased risk of BC [ 14 , 41 , 42 ]. Interaction between XRCC6 genetic polymorphisms and reproductive risk factors is thought by some researchers to contribute to estrogen exposure, which results in double-strand breaks on BRCA1 and BRCA2 DNA and induces BC [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence of CHD might be caused by a combination of genetic variations and maternal lifestyle factors before or during pregnancy. Gene-environment interactions could be deterministic for CHD in individuals who were exposed to environmental risk factors [28]. Recent studies have suggested that the genes related to FA metabolism (i.e., MTHFR, MTRR, MTR, and CBS) might have gene-environment interactions that influence individual susceptibility to CHD [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…We did not find any reports on the study of XRCC6 (Ku70) polymorphisms in the context of thyroid cancer risk. However, there are studies on other tumors [ 58 , 59 , 60 ].…”
Section: Polymorphism Of Genes Encoding Dna Repair Proteins In Thyroi...mentioning
confidence: 99%